A method for gear fatigue life prediction considering the internal flow field of the gear pump. (15th January 2018) - Shen, Haidong; Li, Zhiqiang; Qi, Lele; Qiao, Liang
Abstract: Gear pump is the most widely used volume type hydraulic pump, and it is the main power source of the hydraulic system. Its performance is influenced by many factors, such as working environment, maintenance, fluid pressure and so on. It is different from the gear transmission system, the internal flow field of gear pump has a greater impact on the gear life, therefore it needs to consider the internal hydraulic system when predicting the gear fatigue life. In this paper, a certain aircraft gear pump as the research object, aim at the typical failure forms, gear contact fatigue, of gear pump, proposing the prediction method based on the virtual simulation. The method use CFD (Computational fluid dynamics) software to analyze pressure distribution of internal flow field of the gear pump, and constructed the unidirectional flow-solid coupling model of gear to acquire the contact stress of tooth surface on Ansys workbench software. Finally, employing nominal stress method and Miner cumulative damage theory to calculated the gear contact fatigue life based on modified material P-S-N curve. Engineering practice show that the method is feasible and efficient. Highlights: The 3 dimensional flow field model of gear pump was established. The internal flow field pressure of the gear pump was taken into account. A unidirection flow[HYPHEN]solid coupling model was constructed.